Benefit of vertical localization for sea surface temperature assimilation in isopycnal coordinate model - Wang, Yiguo; Counillon, François; Barthélémy, Sébastien; Barth, Alexander (Frontiers in Climate, 2022)
Sea surface temperature (SST) observations are a critical data set for long-term climate reconstruction. However, their assimilation with an ensemble-based data assimilation method can degrade performance in the ocean interior due to spurious covariances. Assimilation in isopycnal coordinates can delay the degradation, but it remains problematic for long reanalysis. We introduce vertical localisation for SST assimilation in the isopycnal coordinate. The tapering functions are formulated empirically from a large pre-industrial ensemble. We propose three schemes: 1) a step function with a small localisation radius that updates layers from the surface down to the first layer for which insignificant correlation with SST is found, 2) a step function with a large localisation radius that updates layers down to the last layer for which significant correlation with SST is found, and 3) a flattop smooth tapering function. These tapering functions vary spatially and with the calendar month and are applied to isopycnal temperature and salinity. The impact of vertical localisation on reanalysis performance is tested in identical twin experiments within the Norwegian Climate Prediction Model (NorCPM) with SST assimilation over the period 1980--2010. The SST assimilation without vertical localisation greatly enhances performance in the whole water column but introduces a weak degradation at intermediate depths (e.g., 2000-4000 m). Vertical localisation greatly reduces the degradation and improves the overall accuracy of the reanalysis, in particular in the North Pacific and the North Atlantic. A weak degradation remains in some regions below 2000\,m in the Southern Ocean. Among the three schemes, scheme 2) outperforms schemes 1) and 3) for temperature and salinity.